Liderazgo en un centro de atención telefónica de una empresa comercializadora y distribuidora de energía eléctrica en el noroeste de méxico (leadership in a call center of a company marketer and distributor electricity in northwest mexico) - Saavedra, Elena; Galindo Mora, Juan Patricio; Coronado, José (UANL. Facultad de Contaduría Pública y Administración, 2016)
Abstract. Using the Multifactor Leadership theoretical model (Bass and Avolio, 1995) was diagnosed the perceived leadership style by 161 workers of a Regional Call Center of a Mexican public company in charge of distribution and marketing of electricity. We used the short version of the MLQ (Multifactor Leadership Questionnaire), Likert-scaled, validating its internal reliability (Cronbach's alpha for each dimension). Statistical analysis included the overall narrative and the use of structural equations (SPSS 19 and Amos, 19). Model results showed the data are consistent with the proposed research model, with a Chi2 (2)=51.26, df=31, p=0.012,2/df=1.65, RMSEA=0.064, CFI =0.99, NFI=0.96 and TLI=.98). In general, all goodness of fit indicators manifest a good model fit. The results emphasized the importance of a good transactional leadership style complemented by a good transformational leadership style, to achieve good employee extra effort, effectiveness, and satisfaction.